2021
DOI: 10.1002/cre2.495
|View full text |Cite
|
Sign up to set email alerts
|

Association between proton pump inhibitors and periodontal disease severity

Abstract: Objectives: Proton pump inhibitors (PPIs) are commonly prescribed for the management of acid-related gastrointestinal disorders. PPIs modulate osteoclast function, reduce gastric acid secretion, and are associated with the establishment of a more diverse gastrointestinal microbiota. Periodontitis is characterized by microbeassociated host-mediated inflammation that results in loss of periodontal attachment.The aim of this study was to assess whether a relationship exists between PPIs and periodontal disease. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A 2022 cross‐sectional study retrospectively analyzed patients from a university‐based faculty periodontics practice (Chawla et al, 2022 ). The proportion of probing depths ≥ 5 mm or ≥ 6 mm was measured for patients diagnosed with generalized periodontitis, stage III to IV, grade B to C, among PPI users compared to non‐users.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 2022 cross‐sectional study retrospectively analyzed patients from a university‐based faculty periodontics practice (Chawla et al, 2022 ). The proportion of probing depths ≥ 5 mm or ≥ 6 mm was measured for patients diagnosed with generalized periodontitis, stage III to IV, grade B to C, among PPI users compared to non‐users.…”
Section: Resultsmentioning
confidence: 99%
“…The literature describing the relationship of PPIs and teeth was more limited than the relationship between PPIs and implants. We were able to identify five studies describing the effects of PPIs on tissue attachment around teeth, which found an inverse relationship between PPIs and severity of periodontal disease (Chawla et al, 2022; Herrmann et al, 2022b; Yerke & Cohen, 2019; Yerke et al, 2019, 2021). There were no studies that described the effects of PPIs on bone levels around teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain modi able risk factors, such as medications: antiresorptive bone agents [12], antihypertensive drugs [13], statins [14], psychiatric drugs, and proton pump inhibitors [15,16], have been reported to have an impact on periodontal status.…”
Section: Periodontitis and Other Risk Factorsmentioning
confidence: 99%